INFLUENCE OF MEDIA GELLING AGENTS ON ROOT BIOMASS AND IN VITRO VA-MYCORRfflZAL SYMBIOSIS OF CARROT WITH GIGASPORA MARGARITA - NAVEEN PAL BHATIA; ALOK ADHOLEYA; ANJALI VERMA (BIOTROPIA, 1997)
An in vitro study with Ri-TDNA transformed roots of carrot  (Daucus carota) was carried out  to evaluate  the role of macro-elements contributed as impurities in  the gelling agent (phytagel) over and above  those present  in the minimal (M) medium. Production of root biomass was taken as a measure to quantify the influence of macro-elements added to the minimal medium. The levels of phosphorus when adjusted to 1.19 mg/1 and 1.09 mg/l, lead to dry root biomass production at par with the control. Attempts made to lower the amount of impurities in phytagel by de-ionization using different alkalies, proved NaOH to give the best results in terms of relatively high amount of root biomass. In an in vitro dual culture system with carrot as host and Gigaspora margarita as the vesicular-arbuscular mycorrhizal fungus, phytagel impurities helped to produce maximum number of infection units and auxiliary cells when phytagel was added to the minimal medium.Key words:    Agrobacterium    rhiiogenesfDaucus    caro/a/Gelling    agents/diaspora    margarita/Macro- elements/Vesicular-arbuscular mycorrhiza/Transformed roots.